2019
DOI: 10.1093/alcalc/agz054
|View full text |Cite
|
Sign up to set email alerts
|

Probenecid Reduces Alcohol Drinking in Rodents. Is Pannexin1 a Novel Therapeutic Target for Alcohol Use Disorder?

Abstract: Aims The development of novel and more effective medications for alcohol use disorder (AUD) is an important unmet medical need. Drug repositioning or repurposing is an appealing strategy to bring new therapies to the clinic because it greatly reduces the overall costs of drug development and expedites the availability of treatments to those who need them. Probenecid, p-(di-n-propylsulfamyl)-benzoic acid, is a drug used clinically to treat hyperuricemia and gout due to its activity as an inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…67 Spironolactone metabolites canrenone (20) and 7-α-thiomethylspirolactone (23) and the structural analogue eplerenone (24) showed weak dose-dependent inhibition of Panx1. 67 Conversely, structurally related compounds such as aldosterone (21) and progesterone (22) and the functionally related drug finerenone (25) exhibited no effect on Panx1. 67 Panx1 is also inhibited by the P2X7 receptor agonists ATP (26) and benzylbenzoyl-ATP (27) and by the P2X7 receptor antagonists suramin, KN-62, and A438079 (not shown).…”
Section: ■ Pharmacological Inhibition Of Panx1mentioning
confidence: 99%
See 1 more Smart Citation
“…67 Spironolactone metabolites canrenone (20) and 7-α-thiomethylspirolactone (23) and the structural analogue eplerenone (24) showed weak dose-dependent inhibition of Panx1. 67 Conversely, structurally related compounds such as aldosterone (21) and progesterone (22) and the functionally related drug finerenone (25) exhibited no effect on Panx1. 67 Panx1 is also inhibited by the P2X7 receptor agonists ATP (26) and benzylbenzoyl-ATP (27) and by the P2X7 receptor antagonists suramin, KN-62, and A438079 (not shown).…”
Section: ■ Pharmacological Inhibition Of Panx1mentioning
confidence: 99%
“… ,, Viruses such as HIV may be able to exploit Panx pores to gain entry into cells, and it has been hypothesized that some bacterial toxins may cause cell lysis by activating a cascade involving Panx channels . The inhibition of Panx1 has also been shown to alleviate the symptoms of morphine withdrawal and alcohol use disorder in murine models. Conversely, Panx1 expression is reduced in some cancer types and the restoration of Panx1 expression in glioma cells suppressed tumor cell proliferation and motility. , Given the range of biological processes that are connected to Panx1 function, selective modulation of Panx channels with small molecules appears to offer a therapeutic target for multiple important human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Spironolactone via pannexin 1 channel inhibition rapidly lowers blood pressure and inhibits α1-adrenergic activity in mice [83]. We have recently reported that the pannexin 1 channel inhibitor probenecid reduced alcohol drinking in nondependent and dependent rats, as well as binge-like drinking in mice [84]. Overall, future studies are needed to elucidate the exact mechanism(s) of action of spironolactone on alcohol-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For that purpose we used probenecid, a known inhibitor of OAT, a transporter which mediates the transport of several active compounds including KYN (Wu et al, 2017) producing an accumulation of KYN and KYNA in brain (Moroni et al, 1988; Vécsei et al, 1992). Probenecid has been recently described as able to modulate ethanol intake without affecting water or saccharin consumption (Tunstall et al, 2019). However, the authors demonstrated this effect only at elevated doses (200 mg·kg −1 ) and not with the dose used in this study (100 mg·kg −1 ), a result that has been validated in the present manuscript.…”
Section: Discussionmentioning
confidence: 99%